A Delta‐Parallel‐Inspired Human Machine Interface by Using Self‐Powered Triboelectric Nanogenerator Toward 3D and VR/AR Manipulations. Issue 1 (2nd December 2020) - Hou, Cheng; Geng, Jiangjun; Yang, Zhan; Tang, Tianyi; Sun, Yuyang; Wang, Fengxia; Liu, Huicong; Chen, Tao; Sun, Lining
Abstract: In recent years, human‐machine interface technology has entered a period of rapid development in the global scope. It has gradually expanded from the initial field of medical rehabilitation to engineering bionics, virtual reality, space technology, deep‐sea assignments, atomic energy technology, remote education, and other areas. Herein, an innovative, self‐powered delta‐parallel human‐machine interface (DT‐HMI) for 3D sensing and control is proposed. By using three pairs of triboelectric nanogenerator (TENG) sensing gears based on both contact‐separation and sliding modes of triboelectric effect, the positive and negative rotation of the gears and rotation angles can be obtained. According to the forward‐and‐inverse kinematics of parallel robots, the spatial position and motion attitude of the platform can be calculated. The three pairs of TENG sensing gears with six electrodes define the 512 virtual sensing pixels. The low‐cost, simple‐designed DT‐HMI controller can achieve remote control and even spatial position mapping. Accordingly, the combination of output signals enables the realization of a highly scalable and self‐powered triboelectric interface toward a variety of application scenarios, including 2/3D control, VR/AR, interaction, robotics, etc. Abstract : By using three pairs of triboelectric nanogenerator sensing‐gears based on both contact‐separation and sliding modes of triboelectric effect, the positive and negative rotation of the gears and rotation angles can be obtained. The three pairs of TENG sensing gears with six electrodes define the 512 virtual‐sensing‐pixels. The low‐cost, simple‐designed DT‐HMI controller can achieve remote control and even spatial position mapping.